2019
DOI: 10.1080/02640414.2019.1585410
|View full text |Cite
|
Sign up to set email alerts
|

Differences in maturity, morphological and physical attributes between players selected to the primary and secondary teams of a Portuguese Basketball elite academy

Abstract: The present study aims (i) to compare the maturational, morphological and fitness attributes of young basketball players of primary and secondary teams of an elite basketball academy, and (ii) to identify the set of morphological and fitness attributes which better discriminate the players from the two teams. A total of 116 male basketball players of an elite basketball academy were divided into primary (team A) and secondary (team B) teams in two age groups (U-14 and U-16). All the players were evaluated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 49 publications
4
52
0
4
Order By: Relevance
“…Furthermore, there are significant differences between genders in U'14, U'16 and U'18 categories both in the Parts of Circuits variable and in the Distance variable. These differences confirm the results found in the literature where men travel a longer distance at high intensity, while women carry out a greater volume of demands [32][33][34][35][36][37].…”
Section: Anaerobic Capacitysupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, there are significant differences between genders in U'14, U'16 and U'18 categories both in the Parts of Circuits variable and in the Distance variable. These differences confirm the results found in the literature where men travel a longer distance at high intensity, while women carry out a greater volume of demands [32][33][34][35][36][37].…”
Section: Anaerobic Capacitysupporting
confidence: 90%
“…Therefore, during the competition, the athlete is in similar values to those obtained in the test, close to 90% of the HR Max [34]. These differences affect the production of VO2max as it is higher depending on age because it is linked to greater development and body size [35]. In % HR Max, all players are at values higher than 75% of the HR Max during the aerobic test [36].…”
Section: Aerobic Capacitymentioning
confidence: 60%
“…These individual characteristics influence explosive actions or gestures since they are responsible for generating greater contractile force and speed [20]. The differences are also found in the function of age (age-related) since it is a quality that evolves as a function of the evolutionary development of the athletes [21]. Regarding research found in young basketball players, differences in the strength generated by the lower body were observed in a cross-sectional study as a function of age and sex [22].…”
Section: Introductionmentioning
confidence: 99%
“…The requirements of youth sports lead to the age banding of players into training groups and teams; sports administrators age-band players into training groups relative to cutoff dates (e.g., the start and end of the calendar year; Cobley et al, 2009). The assessment of players by trainers during the talent identification (TI) process can be disrupted by differences in the players' biological development (Ramos et al, 2019) and sociological factors (Hancock et al, 2013). Players born closer to the starting point of their age group relative to their peers may be older by as much as 2 to 5 years (Johnson et al, 2017), and the selection of more mature and stronger players will result in an overrepresentation of players born in the first part of the selection period (e.g., quarter).…”
Section: Introductionmentioning
confidence: 99%